Impact of Transcranial Magnetic Stimulation on Functional Movement Disorders: Cortical Modulation or a Behavioral Effect? - Garcin, Béatrice; Mesrati, Francine; Hubsch, Cécile; Mauras, Thomas; Iliescu, Iulia; Naccache, Lionel; Vidailhet, Marie; Roze, Emmanuel; Degos, Bertrand (Frontiers in Neurology, 2017)
Introduction: Recent studies suggest that repeated transcranial magnetic stimulation (TMS) improves functional movement disorders, but the underlying mechanisms are unclear. The objective was to determine whether the beneficial action of TMS in patients with functional movement disorders is due to cortical neuromodulation or rather to a cognitive-behavioral effect. Method: Consecutive patients with functional movement disorders underwent repeated low-frequency (0.25 Hz) magnetic stimulation over the cortex contralateral to the symptoms or over the spinal roots (root magnetic stimulation, RMS) homolateral to the symptoms. The patients were randomized into two groups: group 1 received RMS on day 1 and TMS on day 2, while group 2 received the same treatments in reverse order. We blindly assessed the severity of movement disorders before and after each stimulation session. Results: We studied 33 patients with functional movement disorders (dystonia, tremor, myoclonus, Parkinsonism or stereotypies). The median symptom duration was 2.9 years. The magnetic stimulation sessions led to a significant improvement (>50%) in 22 patients (66%). We found no difference between TMS and RMS. Conclusion: We suggest that the therapeutic benefit of TMS in patients with functional movement disorders is due more to a cognitive-behavioral effect than to cortical neuromodulation.